Research on power communication private network based on interleaved digital-analog hybrid modulation - ZHANG Jun; XU Xiang; RUI Wenjun; HU Weisheng (Dianxin kexue)
Power communication network is an important part to ensure the safe, stable, and economical operation of power grid. The optical fiber transmission system is widely used in the power communication network to provide wide bandwidth. However, there is a signal-to-noise ratio obstacle for high-fidelity transmission. Based on this, an interleaved digital-analog hybrid modulation scheme was proposed. At the transmitter, the original waveform was divided into a discrete digital part and a continuous analog part. At the receiver, the link noise in the digital part was removed by rounding operation, and the spectral efficiency was improved by the linear combination of analog part. Besides, the time-domain interleaving of in-phase and quadrature components reduced the peak-to-average power ratio, and enhanced the effective signal-to-noise ratio under the peak power constraint. In the direct detection-based experiment, after 1 km standard single-mode fiber transmission, the recovered signal-to-noise ratio of 68 GBd signal with interleaved digital-analog modulation could achieve 33.0 dB, which supports the 1 024-ary quadrature amplitude modulation (1 024-QAM) signal with 17 GHz bandwidth. The corresponding bitrate was 170 Gbit/s, and the common public radio interface-equivalent rate was 1 Tbit/s. Both simulation and experimental results indicate that the interleaved digital-analog modulation scheme exhibits a signal-to-noise ratio gain compared with the conventional modulation scheme, and offers a feasible scheme for low-cost, high-bandwidth and high-fidelity power communication network.